Morphological and Optical Tuning of Lead-Free Cs2SnX6 (X = I, Br) Perovskite Nanocrystals by Ligand Engineering - Veronese, Alessandro; Ciarrocchi, Carlo; Marelli, Marcello; Quadrelli, Paolo; Patrini, Maddalena; Malavasi, Lorenzo (Frontiers in Electronics, 2021)
In order to overcome the toxicity of lead halide perovskites, in recent years the research has focused on replacing lead with more environmentally friendly metals like tin, germanium, bismuth or antimony. However, lead-free perovskites still present instability issues and low performances that do not make them competitive as compared to their lead-based counterparts. Here we report the synthesis of lead-free Cs2SnX6 (X = Br, I) nanostructures of different shapes by using various surface ligands. These compounds are a promising alternative to lead halide perovskites in which the replacement of divalent lead (Pb(II)) with tetravalent tin (Sn(IV)) causes a modification of the standard perovskite structure. We investigate the effects of different amines on the morphology and size of Cs2SnX6 (X = Br, I) nanocrystals, presenting a facile hot-infection method to directly synthesize three-dimensional (3D) nanoparticles as well as two-dimensional (2D) nanoplatelets. The amines not only modify the shape of the crystals, but also affect their optical properties: increasing the length of the amine carbon chain we observe a widening in the band gap of the compounds and a blue-shift of their emission peak. Alongside the tuning of the chemical composition and the reduction of the crystal size, our study offers a new insight in controlling the physical properties of perovskite nanocrystals by means of the capping ligands, paving the way for future research on lead-free materials.